Scalable Parallel Programming Applied to H.264/AVC Decoding - Juurlink, Ben.; Alvarez-Mesa, Mauricio; Chi, Chi Ching; Azevedo, Arnaldo; Meenderinck, Cor.; Ramirez, Alex.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
none
Introduction -- Understanding the Application: An Overview of the H.264 Standard -- Discovering the Parallelism: Task-level Parallelism in H.264 Decoding -- Exploiting Parallelism: the 2D-Wave -- Extracting More Parallelism: the 3D-Wave -- Addressing the Bottleneck: Parallel Entropy Decoding -- Putting It All Together: A Fully Parallel and Efficient H.264 Decoder -- Conclusions.
Keywords: Engineering; Computer science; Engineering; Signal, Image and Speech Processing; Programming Techniques